2016
DOI: 10.1155/2016/8564020
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Pressure Distribution among Older Persons with Different Types of Foot and Its Correlation with Functional Reach Distance

Abstract: Background. Changes in biomechanical structures of human foot are common in the older person, which may lead to alteration of foot type and plantar pressure distribution. We aimed to examine how foot type affects the plantar pressure distribution and to determine the relationship between plantar pressure distribution and functional reach distance in older persons. Methods. Fifty community-dwelling older persons (age: 69.98 ± 5.84) were categorized into three groups based on the Foot Posture Index. The plantar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
10
1
1
Order By: Relevance
“…In typically developing adults, foot alignment is related to unilateral sway velocity . The foot postures investigated in this study, pronation, neutral, and supination, each create different plantar pressure distributions . In addition, the length tension relationships of the agonist and antagonist prime movers are altered in each postural deviation.…”
Section: Discussionmentioning
confidence: 99%
“…In typically developing adults, foot alignment is related to unilateral sway velocity . The foot postures investigated in this study, pronation, neutral, and supination, each create different plantar pressure distributions . In addition, the length tension relationships of the agonist and antagonist prime movers are altered in each postural deviation.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study has shown that higher peak plantar pressure beneath the hindfoot and midfoot areas of the foot are associated with lower balance test scores, indicating that proprioception and foot stability are important for predicting foot pressure [14]. Other studies have presented the associations between the level of physical activity and peak plantar pressure in children [15]. Specifically, a study by Mickle et al [15] has shown that higher total physical activity level and time spent in moderate-to vigorous-intensity physical activity are correlated with lower peak pressures across the heel in boys, while no significant correlations between the aforementioned variables in girls were observed.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring peak plantar pressure beneath different foot regions is of significant clinical importance, because it is postulated that older adults with abnormal foot posture and balance performance may be of higher risk of generating higher peak plantar pressure loads [14]. One previous study has shown that total physical activity and time spent in moderate-to-vigorous physical activity are significantly and inversely correlated with peak plantar pressures across the heel region of the foot [15]. Another study using similar methodology has shown similar results, i.e., moderate-intensity, vigorous-intensity and moderate-to vigorous-intensity physical activity are significantly and inversely correlated with peak plantar pressures across the middle and lateral forefoot region and the lateral midfoot region of the foot [16].…”
Section: Introductionmentioning
confidence: 99%
“…Mohd Said et al (Mohd Said et al 2016) by comparing the pressure distribution of the soles of the pronated foot and the supinated foot in the elderly found that the peak pressure of the pronated foot was significantly lower than that of the supinated foot. Tuna et al (Tuna et al 2014) through the intervention of orthotics in the elderly with pronated foot, the results showed that the static balance of patients with pronated foot was unstable, and the use of orthotics has no effect on the balance parameters.…”
Section: Pronated Foot and Supinated Footmentioning
confidence: 99%
“…Mohd Said et al (Mohd Said et al 2016) examined how foot type influences the plantar pressure distribution of older people and turned out that pronated foot showed a significant decrease of max pressure in the forefoot region compared to the supinated foot, specifically in the fourth and fifth metatarsals. Meanwhile, all three-foot types showed no significant differences in contact areas.…”
Section: Supinated and Pronated Footmentioning
confidence: 99%